Iqbāl aur Bazm-i Iqbāl Ḥaidarābād Dakkan - ʻUrūj, ʻAbdurraʼūf (Dāruladab, Pākistān, 1978)
Historical study of the links of Sir Muhammad Iqbal, 1877-1938, with the former Indian state of Hyderabad, Deccan.